The Steps of Language Formation in the Critical Pragmatic Arabic Approach of the Iraqi Theorist Abdulrazak Alghaliby - Dr. Ahmed Muhsen Mashkour; Lect. Majid Dakhil Hammadi; Lect. Hayder Abdulrazak Oudah (International Journal on Humanities and Social Sciences, 2023)
We find Modernity in all aspects of life, and this is what we see in Western Societies and the emergence of several schools of criticism and literature, which is the topic that pertains to our research. The competition of that school, and an example of that, is the emergence of the Structuralism School, Deconstructionism School, and Formalism School, leading to the Arabic Pragmatic Theory, which is the focus of our study. The language and its sciences had their share of this development. The sciences of rhetoric, as well as criticism and its schools, developed until they reached Postmodernity. Arabic Pragmatic Theory(CPAA) is one of these modern literary and critical schools. In its foundations and rules are based on several important pillars, the most important of which is implicature, significance, and the signified aspect. Although sometimes the significance is absent, but the one who predicts it is the signified aspect, as well as it adopted Discourse in language and Perception that pours into the essence of the Concept, and (CPAA) as a scientific theory that took Ethics as an essential aspect in dealing with the Literary Text, whether poetry or narrative, and its difference from other critical theories is that , its reliance on the linguistic vocabulary and the connotations it carries in order that it may give the text strength and Aesthetics in terms of construction and Displacement, so as to provide the text with its elements affecting the reader and the recipient. The most important of these elements are the element of Suspense and the element of Surprise by showing, what is behind the lines and what is between them, and what is in the subsoil of the language.